The influence of epidural versus systemic analgesia on incidence of cardiac complications inelderly with hip fracture - Temelkovska Stevanovska, Marina; Kokareva, Anita; Petreska Ristovska, Blagica; Demjanski, Vasko (Wolters Kluwer, 2015)
Background and Goal of Study: patients with hip fracture are usually older patients. Uncontrolled acute pain and stress of surgery in elderly patients may cause increased cardiac morbidity and mortality (1). Epidural analgesia blocks sympathetic nervous system and reduces the incidence of myocardial ischemia and dysrhythmias and the response to stress (2). The aim of this study was to compare the ef fect of continuous epidural versus general analgesia on the incidence of cardiac complications and their analge- sic effect in patients with hip fracture. materials and methods: Sixty patients with hip fracture older than 65 years with previously defined high per operative cardiac risk according to ACC/AHA guidelines were included and were randomly assigned to two groups of 30 patients: SA group -patients with sistemic analgesia, niflam 2 x 100 mg/iv and tramadol 1 mg/kg/iv every 8 hours; and EDC group - patients with a continu- ous epidural analgesia with bupivacaine 0,125% - 5ml/h and fentanyl 3μg/ml. As end points of the study were registered the incidence of cardiac events in both groups: cardiac death, myocardial infarction, congestive heart failure, unstable angina and new-onset atrial fibrillation. In all patients were deter- mined laboratory parameters and pain intensity by using Verbal Descriptive Scale as well as the side ef fects. Results and Discussion: The epidural analgesia decrease the incidence of per operative cardiac events in patients with high per operative cardiac risk for surgery for hip fracture ( SA group 46,6% vs. 15% in EDC group) and in the same time decrease cardiac mortality (10% in SA group vs. 0% in EDC group).The values of VDS were significantly lower in patients with EDC block versus patients with sistemic analgesia in all experimental times as well as lower number of side ef fects. Conclusion(s): Early administration of continuous epidural analgesia in pa- tients with high per operative risk with hip fracture decrease the incidence of cardiac morbidity and mortality and provide superior pre- and post-operative analgesia comparing sistemic analgesia, with minimal side ef fects. References: 1. Katsanos S.N. Mavrogenis A. F. et al. Current concepts for preoperative cardiovascular evaluation and perioperative care of the elderly with hip fracture. EEXOT 2009; 60:134-141. 2. Auerbach A. Goldman L. Assessing and Reducing the Cardiac Risk of
Keywords: epidural analgesia; perioperative cardiac risk; ACC/AHA classification